Universuum of Institutional Development for Post Production Offshore Platform Decommissioning in Indonesia - Sari Amelia; Ayomi D. Rarasati; A. Jaka Santos (Sekolah Tinggi Manajemen IPMI, 2020)
The objectives of the study are to review current institutional condition for post-production offshore platform decommissioning in Indonesia and to provide an institutional development analysis by applying universuum of institutional development model. This study is one of qualitative research that synthesized data from documentation through literature study. The output of the study is a comparison matrix between universuum of institutional development model and institutional development of post-production offshore platform decommissioning in Indonesia.